Corrosion Rate Analysis in Material Selection for Tubing in CO2 Injection Process at Well K-28 - Disti, Salsabila Meisya; Rubiandini, Rudi (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
This research aims to analyze the corrosion level of the tubing material used in CO2 injection at well K-28. Four types of carbon steel tubing, 13Cr, super 13Cr, and super 15Cr, were analyzed under shut-in and injection conditions using experimental data from a previously published paper titled “Material Selection and Corrosion Rate Analysis for CO2 Injection Well: A Case Study of K1 Field CO2 Sequestration Project”. The research results in eight corrosion rate equations for each condition and type of tubing. Based on the analysis, super 15Cr shows the best corrosion resistance, both in shut-in and injection conditions, with a corrosion rate ranging from 0.00053 mm/year to 0.00085 mm/year at temperatures of 25-35°C and pH 3.08-3.09. The research also showed that the temperature from the surface to the bottom hole and pH had a significant impact on the corrosion rate. Data was processed using Excel and StatsModels library of Python machine learning to estimate the corrosion rate based on these parameters. Super 15Cr is recommended as the most corrosion-resistant tubing material for use in high corrosion potential environments during the CO2 injection process in well K-28. This conclusion is based on a combination of literature studies, experiments, and regression analysis, which identify super 15Cr as the optimal choice for minimizing corrosion risk in this application.